2007
DOI: 10.1016/j.jtcvs.2006.10.022
|View full text |Cite
|
Sign up to set email alerts
|

Clinical condition at mid-to-late follow-up after transatrial–transpulmonary repair of tetralogy of Fallot

Abstract: At mid-to-late follow-up, clinical condition in tetralogy of Fallot corrected according to contemporary surgical approaches appears well preserved. However, even these patients show right ventricular dilation and dysfunction associated with impaired functional capacity. Abnormalities relate to right ventricular outflow tract motion abnormalities, longer interval since repair, longer QRS duration, and more severe pulmonary regurgitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 23 publications
2
33
0
Order By: Relevance
“…Prospective longitudinal studies based on this concept were beneficially applied in LV disease states and should provide improved criteria for treatment strategies in the growing population of patients operated for tetralogy of Fallot. Age at operation should be included as a factor during decision making, which is in accordance with recent observations of the favourable long term outcome in TOF patients [3,11].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Prospective longitudinal studies based on this concept were beneficially applied in LV disease states and should provide improved criteria for treatment strategies in the growing population of patients operated for tetralogy of Fallot. Age at operation should be included as a factor during decision making, which is in accordance with recent observations of the favourable long term outcome in TOF patients [3,11].…”
Section: Discussionsupporting
confidence: 77%
“…Temporal resolution was approximately 40 ms per cardiac phase and 30 phases were reconstructed retrospectively. Imaging parameters were as previously reported [11].…”
Section: Cardiac Magnetic Resonance Imagingmentioning
confidence: 99%
“…They finally concluded that RVOT reconstruction in TOF, using only a limited transannular incision and a stiff Dacron patch, that restricts the pulmonary annulus expansion during the natural growth process, affords the same long-term perspective as in instances where the entire pulmonary annulus integrity can be preserved. This paper is in line with recent publications, advocating surgical repair of TOF by avoiding as much as possible a right ventricular incision and preserving pulmonary valve function (2)(3)(4)(5). Presently, TOF repair should consist of a transatrial transtricuspid approach to close the ventricular septal defect and to resect the obstructive infundibular muscle bundles, and a transpulmonary access to tackle the pulmonary valve component and eventually the hypoplasia of the pulmonary artery.…”
supporting
confidence: 78%
“…6 This may cause reduced RV and LV diastolic and systolic performance. 22 Although the RV global diastolic performance measured by Doppler blood flow in our patients with ToF was within the normal range, TDI measurements in the RV walls confirm that RV regional diastolic dysfunction exists.…”
Section: Downloaded Frommentioning
confidence: 99%
“…The reluctance to exercise in these patients may in part result from fear of a negative effect of exercise on their heart. [3][4][5][6] Of all patients with ConHD, patients with tetralogy of Fallot (ToF) are among those with a high chance of developing heart failure. 7 As such, they may be considered to benefit most from exercise training.…”
mentioning
confidence: 99%